The Influence of Organizational Culture and Work Environment on Job Satisfaction with Work Motivation as an Intervening Variable - Kartina Eka Ningsih; Jais, Achmad; Akbar, Ali; Johansyah (Universitas Muhammadiyah Pontianak, 2026)
This study examines the effects of organizational culture and work environment on job satisfaction, with work motivation as an intervening variable, at PT Putralintas Mandiritama. The objective is to analyze direct and indirect relationships among these variables. A quantitative approach was used with a census of 54 employees, and data were analyzed using PLS-SEM with SmartPLS 4. The results show that the work environment and work motivation significantly affect job satisfaction, while organizational culture does not. Work motivation mediates the effect of work environment on job satisfaction. These findings highlight the importance of improving workplace conditions to enhance employee satisfaction.